Exploring how security features affect the use of electronic health records. (17th May 2010) - Hewitt, Barbara
While individuals in most organisations routinely use computers to conduct business, few healthcare organisations have Electronic Health Record Systems (EHRS). Healthcare organisations face many obstacles and challenges when implementing EHRS including healthcare staff and physician resistance, security issues, and costs. While previous studies explored physician and healthcare organisation adoption issues, this study uses Smart PLS to explores why staff members resist EHR usage using a hybrid Technology Acceptance Model (TAM). It examines whether security measures including biometrics for authentication purposes, multiple access features provided to healthcare provider, and use of Single Sign-On (SSO) systems influences these individual's attitude toward EHRS.